Effect of increasing vinasse doses, in association with different harvest times, on sweet sorghum production - PEREIRA, Ayrton Dourado; TAVEIRA, José Henrique da Silva; FERNANDES, Patrick Bezerra; SILVA, Patrícia Costa; COSTA, Adriana Rodolfo; ARAUJO, Carolina Marques Costa; GIONGO, Pedro Rogério; GURGEL, Antonio Leandro Chaves; CORIOLETTI, Níbia Sales Damasceno (Food Science and Technology, 2024)
The aim of this study was to verify the effect of increasing vinasse doses and different harvest times on the production of sweet sorghum (Sorghum bicolor, L. Moench) grown in clayey soil. The experiment was carried out in the experimental area of the Universidade Estadual de Goiás, Brazil. The experimental design used was completely randomized, in a factorial scheme, set up as follows: five doses of vinasse (0, 50, 100, 150, and 200 m³ ha-1) and two harvest times (69 and 90 days after sowing). There was a 19% increase in forage biomass 90 days after sowing. A vinasse dose effect on forage biomass was observed (p = 0.008); thus, as vinasse supply increases, forage production increases as well. For juice yield, there was an interaction between harvest time and vinasse doses (p = 0.035); 69 days after sowing, a juice production of 6.97 m³ ha-1 was estimated when 190 m³ ha-1 of vinasse was used. Regardless of harvest time, using vinasse in increasing doses promotes significant increases in the production of sweet sorghum biomass. Although the flowering regulator inhibited panicle production, it did not lead to increases in juice production 90 days after sowing.